A study of heat transfer in forced convective drying with the application of laser-induced fluorescence thermometry - Fanning, Eoin (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2016)
Industrial drying is a highly energy-intensive process accounting for up to 25% of energy consumption in some developed countries. While there is a wide range of literature on the topic of drying, the majority of studies focus on specific materials and processes. Furthermore, there are few studies which consider local heat transfer effects on drying. Recently, this has become a fast-developing topic of study in numerical work using two-dimensional and three-dimensional computational fluid dynamics simulations. However, there is not a wide range of experimental work in which the influence of local heat transfer behaviour is studied. In order to study local heat transfer, complex arrangements of thermocouples or infra-red thermography are typically used to measure the surface temperature. A novel two-dimensional temperature measurement technique involves the use of laser-induced fluorescence in which temperature fields of the fluid can be inferred from fluorescence images. However, this technique has been employed scarcely in low temperature heat transfer problems involving gases. This study investigates two-dimensional heat transfer in drying and evaluates the use of LIF thermometry as a technique for convective drying as well as other low temperature heat transfer problems. An experimental model was developed, using an instantaneous mass measurement system and infra-red thermography to study the time evolution of the mass (or the moisture content) and the surface temperature distribution of a saturated porous cube. A laser-induced fluorescence experimental setup has been designed to validate and calibrate the relationship between fluorescence intensity and temperature, for toluene vapour excited with a 266 nm laser sheet, over a small temperature scale. This experimental setup was then extended to a flow tunnel and used to measure temperature fields surrounding a heated cylinder (convective heat transfer) and then a drying porous cube (convective heat and mass transfer). This technique was also tested using an emerging fluorescent tracer material, anisole, for which there are only a few studies to date. The relationship between toluene fluorescence intensity and temperature was validated over a temperature scale significantly smaller than in previous studies. Despite some inaccuracy in inferring temperature measurements, it was found that laser-induced fluorescence thermometry can be applied successfully in low temperature scales and used as a tool for studying heat transfer distribution across solid geometries. Using the single colour technique, the error of temperature measurement was found to range between 2C and 10C for temperatures of 20C and 95C, respectively. This is comparable to the error ranges of previous studies. A novel method for increasing the temperature-sensitivity by time-resolving the fluorescence signal has also been proposed. This led to a 50% increase in the sensitivity of the temperature measurements. This technique has not been performed to date and is particularly useful for low temperature scales where the sensitivity between fluorescence intensity and temperature is limited. During the constant drying rate period of the drying experiments, determination of heat and mass transfer coefficients meant that the analogy between heat and mass transfer in drying could be examined. These results indicated that the analogy between heat and mass transfer is not likely to hold for intense drying conditions (flow rate and temperature). This is an important finding since many numerical drying models rely on the analogy to calculate heat and mass transfer coefficients. It is hypothesized that this may be related to an imbalance between the rate of convective heat transfer and moisture supply to the cube edges, which the temperature distributions across the surface suggest. The laser-induced fluorescence temperature measurements demonstrate a thin thermal boundary layer at the corners facing the flow which supports this theory. These results demonstrate the value of two-dimensional temperature measurements for developing a deeper understanding of heat and mass transfer behaviour in drying.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin